O sentido do trabalho e a identidade do executivo brasileiro: estudo de caso sobre os impactos da demissão - Mascarenhas, Karen Louise (2008)
This qualitative study is focused on the relationship between the executive and the organization. Semi-structured interviews with seven executives which experienced loosing their jobs, were analyzed using the discourse method. The business world context was analyzed considering two cuts: economic-political and social-ideological. The discussion of the relation individual organization, is base on psychosociology appropriate to organizations, focused on imaginary function, organization coercion power and the consequent submission of the executive through the adequation process to the demands for career growth. The impacts of the job contract rupture on the professional identity of the executive are also highlighted, as well as the difficulties in organizing day-to-day routines due to the loss of business routine. Conclusions are that to overcome the dependency link with the organization, executives should be aware of the mechanisms present in the relation and the impacts generated by unbalanced connections and base themselves in developing a more complete identity seeking for realization on what they care for